Biosynthesis of terpenoid indole alkaloid : molecular cloning, characterization and expressions of dxr genes from mitragyna speciosa (Roxb.) Korth - Juraithip Wungsintaweekul (Prince of Songkla University, 2010)
The Committee of Higher Education and the Thailand Research Fund